2017
DOI: 10.20959/wjpr201711-9633
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Kigelia Africana

Abstract: It occurs widely in Africa and beyond is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The detection of all these classes of biologically active compounds in the different extracts of the kigelia fruit were consistent with its use in the treatment of various conditions [33] [34]. The particular presence of flavonoids, phenols, quinones, anthraquinones justified the use of the fruit in the treatment of male infertility because of its androgenic and antioxidant properties [15] [35] [36].…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…The detection of all these classes of biologically active compounds in the different extracts of the kigelia fruit were consistent with its use in the treatment of various conditions [33] [34]. The particular presence of flavonoids, phenols, quinones, anthraquinones justified the use of the fruit in the treatment of male infertility because of its androgenic and antioxidant properties [15] [35] [36].…”
Section: Discussionmentioning
confidence: 71%
“…The fruit, edible by several mammalian species, contains flavonoids, terpenes, tannins, steroids, saponins and caffeic acid [9]- [14]. It is included in herbal prescriptions especially for treatment of infertility, poor libido, sexual asthenia and impotence [15]. In particular, the fruit is known to improve fertility in males.…”
Section: Introductionmentioning
confidence: 99%
“…Study conducted by Asoso et al (2019) reported that mortality increased with increased in the concentration of the extracts. An extract with LC50 greater than 1000 µg/ml) in the Artemia nauplii bioassay have been reported to be non-toxic (Halder and Sharma (2017). This activity exhibited by MKaF could be attributable to its endowed pheolic compounds.…”
Section: Resultsmentioning
confidence: 99%
“…Every component of the plant, including the fruit, bark, roots, and leaves, is used medicinally. For example, a decoction of the stem bark has been used to treat kidney disorders, diarrhea, cough, inflammation, renal ailments, fainting, epilepsy, rheumatism, sickle-cell anemia, psoriasis, eczema, and central nervous system depression (Halder;Sharma, 2017;Abbas et al, 2024). Leaves and stem bark have been used for treating dysentery, constipation, and fevers, and as an abortifacient.…”
Section: Introductionmentioning
confidence: 99%